(untitled) (Revista Venezolana de Salud Pública, 2018)
The work examines the conceptions of health, community and participation, later to analyze the community participation in health, since he has understood himself under the dominant paradigm of the biomedicine. Of equal way, it explains as the community participation is directly related what is understood by health and participation on the part of the diverse actors involved in the process.